2013
DOI: 10.1002/app.39196
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the mixing time on the phase structure and glass‐transition behavior of poly(ethylene terephthalate)/poly(ethylene‐2,6‐naphthalate) blends

Abstract: Blends of poly(ethylene terephthalate) and poly(ethylene-2,6-naphthalate) (70 : 30 w/w) were prepared via a melt-mixing process at 280 C with various mixing times. The melt-mixed blends were analyzed by magnetic resonance spectroscopy, differential scanning calorimetry, dynamic mechanical measurements, transmission electron microscopy, and tensile tests. The results indicate that the blends mixed for short times had lower extents of transesterification and were miscible to a limited extent. The blends initiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…The observed behavior of the sequence length and the degree of randomness in this study are consistent with previous reports of the copolymerization of PET/PEN and PET/PBT …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The observed behavior of the sequence length and the degree of randomness in this study are consistent with previous reports of the copolymerization of PET/PEN and PET/PBT …”
Section: Resultssupporting
confidence: 93%
“…This suppression in T mB becomes more exaggerated with reaction time. Experimental studies have previously shown that substantial T m depression is observed in the copolyesters of PET/PEN, PET/PBT, PBT/PBS, PBT/PBN, and PBN/poly(butylene adipate) . Lu and Windle observed the same trend in T mB independent of whether the samples had been quiescently or strain crystallized.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…A desirable combination of PET and PEN can be achieved through blending. The phase structure, transesterification reaction, crystallization, and physical characteristics of TN blends have been studied, which revealed distinct miscibility levels for each blend. When molten PET and PEN are blended, a transesterification reaction occurs, which results in the formation of block copolymers, with increasingly random distribution as the reaction proceeds. , Khonakdar et al studied the transesterification reaction and copolymer structure formation for various average sequence block lengths and degrees of randomness. A decrease in the block length results in an incease in elasticity and relaxation time .…”
Section: Introductionmentioning
confidence: 99%
“…As the reaction progresses, the sequence length L T and L N gradually decreases and degree of randomness B increases, depending on the ester exchange reaction rate. The observed behavior of the sequence length and the degree of randomness are consistent with previous reports of the copolymerization of PET/PEN …”
Section: Resultsmentioning
confidence: 97%